Analisis Pengaruh Penerapan Digital Marketing terhadap Penjualan Produk bagi Usaha Mikro dan Kecil dengan Pandemi Covid-19 sebagai Variabel Moderasi - Rudi Irwanto; Demitrius Kristiyono (Keizai, 2021)
The purpose of this study was to determine the effect of Digital Marketing, on Sales products and determine the effect of Digital Marketing with ease of Pandemic Covid-19 as a moderating variable on Sales Products in small and micro scale enterprises in Kota Besi with the ease of Pandemic Covid-19 as a moderating variable. As for what is presented as a population of enterprises in Kota Besi, the criteria of Micro and Small business of Kota Besi. The Sample taken in the study obtained 130 respondents, divided into 68 respondents who used Digital Marketing, and 62 respondents not use Digital Marketing. The sampling technique used is Convenience Sampling. The research instrument was in the form of a questionnaire using a Likert scale to collect data on variable Digital Marketing, covid-19 pandemic, and sales products, using the MRA (Moderating Regression Analysis). The results of this research indicate that Digital Marketing has a significant and positive effect on product sales. Another result of this research shows that the Covid-19 Pandemic is not a moderating variable in the relationship between Digital Marketing and Product Sales. The Covid-19 Pandemic is an independent variable (predictor) in relation to Product Sales.